Use of tissue microarray for interlaboratory validation of HER2 immunocytochemical and FISH testing. Issue 11 (27th October 2004) - Kay, E; O'Grady, A; Morgan, J M; Wozniak, S; Jasani, B
Abstract : Aims: To evaluate the use of tissue microarray (TMA) technology as a validation tool for HER2 testing by both immunocytochemistry (ICC) and fluorescence in situ hybridisation (FISH) in the diagnostic setting. Methods: TMA constructs from 57 cases of breast cancer were evaluated for HER2 (by ICC and FISH) by two centres. The results were compared. Results: There was a high level of concordance for both ICC and FISH. In five "discrepant" cases only three would have had a potential impact on patient management. Conclusions: Validation of HER2 analysis in the clinical setting by ICC and FISH is essential. The use of TMAs provides for an economy of scale and would be practical in the setting of interlaboratory and intralaboratory validation. It is suggested that routine HER2 ICC and FISH should continue to be performed in laboratories on whole sections. Following this, TMAs would be constructed for all cases of breast cancer. ICC and FISH would be performed on these to validate the results. The TMAs would be available for circulation to other centres for validation purposes. The standardisation of testing between centres, the potential difficulty of minimum case numbers, and the workload issues surrounding validation would all be facilitated by this approach.